Insertion and C–C coupling processes in reactions of the unsaturated hydride [W2Cp2(H)(μ-PCy2)(CO)2] with alkynes. Issue 12 (22nd February 2016) - Alvarez, M. Angeles; García, M. Esther; García-Vivó, Daniel; Ruiz, Miguel A.; Vega, M. Fernanda
Abstract : Alkyne insertion into the W–H bond invariably occurs in the title reactions, to give alkenyl complexes which may undergo further alkyne addition to yield hydrocarbyl-bridged derivatives generated from alkenyl–alkyne coupling. Abstract : The title compound reacted with p -tolylacetylene at room temperature to give the 32-electron σ:π-bound alkenyl complexes trans -[W2 Cp2 {μ–κ:η 2 -C( p -tol)CH2 }(μ-PCy2 )(CO)2 ] and trans -[W2 Cp2 {μ–κ:η 2 -CHCH( p -tol)}(μ-PCy2 )(CO)2 ], with the former complex fully rearranging into the latter one after 1 h at 363 K. Both compounds exist in solution as an isomeric equilibrium mixture (rapid on the NMR timescale) involving the alternate π-coordination of the alkenyl ligand to each of the tungsten atoms. In the presence of CO or certain solvents (THF or CH2 Cl2 ) the α-substituted alkenyl complex was transformed instead into the cis -dicarbonyl isomer cis -[W2 Cp2 {μ–κ:η 2 -C( p -tol)CH2 }(μ-PCy2 )(CO)2 ] (W–W = 2.7273(8) Å). In contrast, the β-substituted alkenyl complex reacted with CO to give the saturated tricarbonyl [W2 Cp2 {μ–κ:η 2 -CHCH( p -tol)}(μ-PCy2 )(CO)3 ], and with excess alkyne (under moderate heating) to yield the alkyne/alkenyl complex [W2 Cp2 {μ–κ:η 2 -CHCH( p -tol)}(μ-PCy2 ){η 2 -CHC( p -tol)}(CO)], with both products also displaying a cisoid disposition of the Cp ligands. In contrast, reactions of the title hydride with tert -butylacetylene were significantly slower and led to very air-sensitive compounds, the only isolable product from these reactions being the oxo alkenyl complex trans -[W2 Cp2 {μ–κ:η 2 -CHCH( t Bu)}(O)(μ-PCy2 )(CO)]. The title hydride reacted with methyl propiolate at room temperature to give selectively the α-substituted alkenyl complex cis -[W2 Cp2 {μ–κ:η 2 -C(CO2 Me)CH2 }(μ-PCy2 )(CO)2 ], but yielded instead the dienyl complex [W2 Cp2 {μ–κ 2 :η 3 -CH(CO2 Me)CHC(CO2 Me)CH}(μ-PCy2 )(CO)2 ] (W–W = 2.944(1) Å) when the reaction was carried out at high temperature (393 K), with the latter generated from an alkenyl/alkyne C–C coupling process. The title hydride also reacted with dimethyl acetylenedicarboxylate, to give three products mainly depending on the reaction temperature; at moderate temperature (343 K) this reaction led exclusively to the saturated alkenyl complex trans -[W2 Cp2 {μ–κC, κO :η 2 -C(CO2 Me)CH(CO2 Me)}(μ-PCy2 )(CO)2 ] (W–W = 2.9329(8) Å), in which the σ:π-bound alkenyl ligand is additionally coordinated through the oxygen atom of the carboxylate group so as to render a O, C : C, C ′ five-electron coordination mode. At 273 K this reaction led instead to a mixture of the unsaturated alkenyl cis -[W2 Cp2 {μ–κ:η 2 -C(CO2 Me)CH(CO2 Me)}(μ-PCy2 )(CO)2 ] and the dienyl complex [W2 Cp2 {μ–κC, κO :η 2 -C(CO2 Me)C(CO2 Me)C(CO2 Me)CH(CO2 Me)}(μ-PCy2 )(CO)2 ] (W–W = 3.0273(6) Å).